Cytoskeletal re-arrangement in TGF-beta1-induced alveolar epithelial-mesenchymal transition studied by atomic force microscopy and high-content analysis - EHRHARDT, CARSTEN; DAVIES, ANTHONY; MEDINA MARTIN, CARLOS (My University, 2012)
Epithelial-mesenchymal transition (EMT) is closely implicated in the pathogenesis of idiopathic pulmonary fibrosis. Associated with this phenotypic transition is acquisition of an elongated cell morphology and establishment of stress fibres. The extent to which these EMT-associated changes influence cellular mechanics is unclear. We assessed the bio-mechanical properties of alveolar epithelial cells (A549) following exposure to TGF-?1. Using atomic force microscopy, changes in cell stiffness and surface membrane features were determined. Stimulation with TGF-?1 gave rise to a significant increase in stiffness, which was augmented by a collagen I matrix. Additionally, TGF-?1-treated cells exhibited a rougher surface profile with notable protrusions. Simultaneous quantitative examination of the morphological attributes of stimulated cells using an image-based high-content analysis system revealed dramatic alterations in cell shape, F-actin content and distribution. Together, these investigations point to a strong correlation between the cytoskeletal-associated cellular architecture and the mechanical dynamics of alveolar epithelial cells undergoing EMT.
PUBLISHED
Keywords: Clinical medicine; Respiratory systems; Epithelial-mesenchymal transition (EMT); Pulmonary fibrosis; Actin fibres; extracellular matrix; scanning probe microscopy; A549 cell line; Nanoscience & Materials